Viability of WiMax for Smart Grid Distribution Network - Aguirre, Jorge Federico (2013)
Smart Grids require a robust communication network to handle huge amount of data involving different smart devices. Wireless applications become the core of advance meter communication systems. The current advances within this area infer that this type of systems will fulfill the Smart Grid requirements for applications such as Advance Metering Infrastructure, Distribution automation or Demand Response. The objective of this paper is to provide a methodology to characterize and to measure the link quality of a wireless communication system applied to different Smart Grid scenarios.